Availability and usage of Knowledge Management: (Decision support for IT and IT Enabled Services in IT Service Industry) - Dr. Tapesh Chandra Gupta, Barakath Ali Shaik Mohamed, Ramanigopal C.S (International Journal of Advanced Science and Technology, 2020)
Many Information Technology service provider organizations have either implemented or are in the process of implementing the Information Technology Library (ITIL) framework to continuously measure and monitor their Information Technology operations to improve service delivery and customer support quality. ITIL is a assortment of best follows for Information Technology service management which provides framework, guidelines, and methodology in Service Approach, Service Enterprise, Service Changeover and Service Action process areas. Knowledge Administration is a critical course in Service Evolution phase of Information Technology Service Management. While few larger service providers through experience have matured their service management process over the years, many small, medium, and few large organizations still face significant challenges in improving service management processes. Repeatable processes and services could be automated by combining market automation tools for knowledge management and Information Technology service management.Global business environment becomes increasingly competitive; there is a growing need for service-based organizations to adopt best practices, tools and methodologies for ITSM. ITIL is a set of ITSM best practices and is now widely embraced by the industry. Implementation of ITIL, however, is complex, costly and time consuming. Enterprises designing, adopting and providing ITSM services often select different methods and designs depending on the business environment and need for similar implementations of ITSM solutions. Organizations rely heavily on the Knowledge to support the business. Advances in technology, innovations, frameworks and policies are practically every day evolving globally. KM is a serious and vibrant structural resource that helps in the global competitive business environment to reach competence, effectiveness and viable gain. This study aims at understanding the implementation and use of KM in the organization of IT service providers. This study used primary data containing incident tickets. This study explores how incident management processes can be improved by effective implementation of the ITIL framework and use of knowledge management in IT service provider companies.